Strength and conditioning for team sports. Sport-specific physical preparation for high performance - Gamble, P. (Routledge, 2013)
Strength and Conditioning for Team Sports is designed to help trainers and coaches to devise more effective high-performance training programs for team sports. This remains the only evidence-based study of sport-specific practice to focus on team sports and features all-new chapters covering neuromuscular training, injury prevention and specific injury risks for different team sports. Fully revised and updated throughout, the new edition also includes over two hundred new references from the current research literature.